Personality traits and interpersonal behaviors in romantic couples - Alexandra L. Halberstadt; Katherine M. Thomas; Aaron L. Pincus; Christopher J. Hopwood (International Journal of Personality Psychology)
The relationship between personality traits and moment-to-moment interpersonal behavior is influenced by the context of the interaction. The aim of the current study was to understand associations between personality traits and interpersonal warmth and dominance in heterosexual romantic couples (Ncouples = 140). Actor-Partner Interdependence Models were used to examine the relationships between interpersonal behavior and the traits of negative emotionality, positive emotionality, and constraint. Results suggested personality traits were associated with behaviors of both the actor and partner, with the strongest positive relationships found between positive emotionality and warm behavior and between negative emotionality and cold behavior. These results provide evidence that personality traits are related to momentary behaviors in romantic couples.